# Recently came across to solve system of linear differential equation with the matrix method, I have

Recently came across to solve system of linear differential equation with the matrix method, I have learnt that the eigenvectors forms part of the complementary function.
A matrix method such as :
$\frac{dy}{dt}=5x+7y$
$\frac{dx}{dt}=9x+4y$
which then we replace a vector x =(x,y) and a matrix M with entries (57,94)
Is there any reason for this (such as the one in ordinary Differential equation is due to the fact that the exponential is the eigenfunction if the differential which also exist as a matrix method, but why the eigenvectors in the front of it?)
You can still ask an expert for help

• Questions are typically answered in as fast as 30 minutes

Solve your problem for the price of one coffee

• Math expert for every subject
• Pay only if we can solve it

e4mot1ic5bf
Make a variable substitution. If you have a homogeneous linear system of ODEs $\stackrel{˙}{x}=Ax$, where A has a basis of eigenvectors ${v}_{1},\dots ,{v}_{n}$ and corresponding eigenvalues ${\lambda }_{1},\dots ,{\lambda }_{n}$, then make a substitution in terms of a new vector variable y, the coordinate vector of x with respect to ${v}_{1},\dots ,{v}_{n}$. Then,
$x={y}_{1}{v}_{1}+\dots +{y}_{n}{v}_{n}⇒\stackrel{˙}{x}={\stackrel{˙}{y}}_{1}{v}_{1}+\dots +{\stackrel{˙}{y}}_{n}{v}_{n}.$
Hence, the system becomes,
$\stackrel{˙}{x}=Ax$
${\stackrel{˙}{y}}_{1}{v}_{1}+\dots +{\stackrel{˙}{y}}_{n}{v}_{n}=A\left({y}_{1}{v}_{1}+\dots +{y}_{n}{v}_{n}\right)$
$={y}_{1}A{v}_{1}+\dots +{y}_{n}A{v}_{n}$
$={\lambda }_{1}{y}_{1}{v}_{1}+\dots +{\lambda }_{n}{y}_{n}{v}_{n}.$
By the linear independence of ${v}_{1},\dots ,{v}_{n}$, we may equate the (non-constant, but still scalar) coefficients of ${v}_{i}$ to obtain
${\stackrel{˙}{y}}_{i}={\lambda }_{i}{y}_{i}$,
for each i. In other words, we have now decoupled the system into n totally independent first order ODEs, in terms of the coordinates of y. These have the usual solutions:
${y}_{i}={A}_{i}{e}^{{\lambda }_{i}t}$,
for some constant ${A}_{i}$. Thus, changing back,
$x={y}_{1}{v}_{1}+\dots +{y}_{n}{v}_{n}={A}_{1}{e}^{{\lambda }_{1}t}{v}_{1}+\dots +{A}_{n}{e}^{{\lambda }_{n}t}{v}_{n}$.
Katey Guzman